Spelling Out Focus‐Fronting Chains and Wh‐Chains: The Case of Italian. (7th May 2019) - Bianchi, Valentina
Abstract: This article tackles the optionality of focus fronting in Italian in terms of alternative spellout of the highest or lowest link of a movement chain. The two options are equally optimal in that the highest link satisfies Scope Transparency while the lowest link, bearing [focus] and attracting the nuclear pitch accent, satisfies Rightmostness; on the other hand, spellout of intermediate chain links satisfies neither principle, and it is therefore suboptimal. As for interrogative wh‐ chains, it is argued that Rightmostness is nonapplicable, because in Italian the lowest link of the wh‐ chain does not possess the [focus] feature; consequently, Scope Transparency always selects the highest chain link as the optimal spellout option.